Gender Differences in Job Burnout, Career Choice Regret, and Depressive Symptoms Among Chinese Dental Postgraduates: A Cross-Sectional Study - Yan, Li; Zhong, Xiaogang; Yang, Lu; Long, Huiqing; Ji, Ping; Jin, Xin; Liu, Li (Frontiers in Public Health, 2022)
Background Job burnout, career choice regret, and depressive symptoms among medical students have received widespread attention. However, little is known about the role of gender in these areas for dental postgraduates. This study aimed to explore gender differences in job burnout, career choice regret, and depressive symptoms among Chinese dental postgraduates. Methods The data were collected from an epidemiological survey conducted by our group from February 2021 to March 2021. We used a self-administered questionnaire covering demographic characteristics, the Maslach Burnout Inventory, the Primary Care Evaluation of Mental Disorders scale, and the Career Choice Regret scale. Univariate and multivariable analyses were performed to explore influencing factors. Results A total of 558 valid dental postgraduate questionnaires were included in this study. The prevalence of job burnout, career choice regret, and depressive symptoms exceeded 30% in males and females. The prevalence of job burnout was 4.7% higher in females than in males; career choice regret was 12.2% higher in females than in males (P < 0.05), and depressive symptoms were 4.9% higher in females than in males. The multivariable analysis showed that factors associated with job burnout for males were sleep time and career choice regret for females. The influencing factors on career choice regret for females were postgraduate entrance examination score, sleep time, and job burnout. Depressive symptoms were a common influencing factor for job burnout and career choice regret in male and female dental postgraduates. Also, job burnout and depressive symptoms had the highest odds ratio for influencing factors on each other. Conclusion Over 30% of dental postgraduates suffered from job burnout, career choice regret, and depressive symptoms, and incidences were higher in females. A discrepancy of influencing factors existed between male and female dental postgraduates. Targeted measures should be taken to change this situation.